The influence of the skin tumors excision width in the postoperative facial asymmetry - Milićević, Saša; Jevtić, Aleksandar; Stepić, Nenad (Vojnosanitetski pregled, 2021)
Background/Aim. Planning an elliptical excision of the facial skin, caused by lines of minimum tension, is very important in order to achieve good aesthetic results. The width of the tumor excision affects the possibility of a direct closure of the post-excision defect. The aim of the study was to determine the minimum width of excision that does not affect postoperative symmetry of the face, in relation to the preoperative one, using an objective scanning method with a line laser scanner. Methods. The study included 50 patients of both sexes, older than 50 years, who had verified facial skin tumor and established medical indication for surgical elliptical excision and direct suture. All patients had laser scanning preoperatively, and then seven days and 90 days postoperatively, giving x, y, and z coordinates of 5 cephalometric points on the face, which determined the shape of the examined region. Patients were divided into three groups depending on the width of the excision (< 10 mm, 10–15 mm, > 15 mm). The shape of the examined region among different width of excision was compared, preoperatively, 7 days and 90 days postoperatively, using Procrustes analysis and analysis of the coordinates of cephalometric points. Results. Taking into account preoperative and postoperative x, y and z coordinates of the cephalometric points, statistically significant differences between the group of patients with the width excision < 10 mm and the other two groups (excision width 10–15 mm and > 15 mm) were found. Conclusion. The width of the skin tumors excision < 10 mm does not affect the postoperative facial asymmetry when a post-excisional defect is closed by direct suture.